ADVANCES IN CELIAC DISEASE: DIAGNOSIS, NEW TREATMENTS AND GLUTEN FREE DIET UPDATED RECOMMENDATIONS - SASSI SOUFIANE (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2023)
Celiac disease is an immune-mediated disorder triggered by a protein found in lots of our daily life's products called gluten, which leads to a gradual disappearance of intestinal villi. The disease can occur at any stage of life and manifests with nonspecific symptoms. The diagnosis of celiac disease is confirmed through immunohistological testing. The only effective therapeutic approach is a strictly followed gluten-free diet. New alternatives to the clinical and preclinical gluten-free diet are currently being researched. Throughout this work, we will discuss the challenges faced by patients, common mistakes to avoid, basic information for sourcing meals, as well as the role of doctors and pharmacists in managing celiac disease. We will also explore the advances in celiac disease in term of diagnosis and recommendations.
Keywords: Celiac Disease; Diagnosis of Celiac Disease; Gluten-Free Diet recommendations; Management of Celiac Disease; Maladie cliaque; Diagnostic de la maladie cliaque; Recommandations pour un régime sans gluten; Gestion de la maladie cliaque )( )